Private Higher Education and Regional Inequalities: The Ethiopian Experience - Gidey, Tilahun; Teixeira, Pedro (International Higher Education, 2011)
Over the last decade, Ethiopia has seen a major leap in education enrollment. The private sector has provided a significant contribution to this expansion, notably in higher education. The expansion of higher education has been accompanied by an attempt on the part of the government to establish at least one university in each regional state. Regional diversification and the quality evaluation process are the coning issues, which will certainly feature increasing tension between the private sector and the government.